(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: This study aimed to compare soft tissue changes observed in Class III skeletal deformity patients treated with either single-jaw surgery (mandibular setback via Bilateral Sagittal Split Osteotomy - BSSO) or two-jaw surgery (maxillary advancement via Le Fort I combined with mandibular setback via BSSO). Methods: A retrospective study was conducted on 40 treated Class III patients, divided into two groups based on the assigned surgical procedure: Group I underwent single-jaw surgery involving only mandibular setback (20 patients), and Group II underwent two-jaw surgery (20 patients). Results: Upper lip changes were observed in both groups, but the magnitude of change was significantly greater in the two-jaw surgery group. Patients in both groups showed marked improvement in facial soft tissue profiles, effectively correcting the concave facial appearance. Conclusion: When comparing soft tissue changes between Class III patients treated with single-jaw versus two-jaw surgery, significant differences were noted in specific parameters such as facial convexity, maxillary prominence, and upper lip prominence.